A Class of Protein-Coding RNAs Binds to Polycomb Repressive Complex 2 and Alters Histone Methylation - Liao, Meijian; Sun, Xiaolin; Gao, Shoucui; Zhang, Yaou (Frontiers in Oncology, 2021)
Polycomb repressive complex 2 (PRC2) is a multi-subunit protein complex mediating the methylation of lysine 27 on histone H3 and playing an important role in transcriptional repression during tumorigenesis and development. Previous studies revealed that both protein-coding and non-coding RNAs could bind to PRC2 complex. However, the functions of protein-coding RNAs that bind to PRC2 complex in tumor are still unknown. Through data mining and RNA immunoprecipitation (RIP) assay, our study found that there were a class of protein-coding RNAs bound to PRC2 complex and H3 with tri-methylation on lysine 27. The Bayesian gene regulatory network analysis pointed out that these RNAs regulated the expression of PRC2-regulated genes in cancer. In addition, gene set enrichment analysis (GSEA), gene ontology (GO) analysis, and weighted gene co-expression network analysis (WGCNA) also confirmed that these RNAs were associated with histone modification in cancer. We also confirmed that MYO1C, a PRC2-bound transcript, inhibited the modification level of H3K27me3. Further detailed study showed that TMEM117 regulated TSLP expression through EZH2-mediated H3K27me3 modification. Interestingly, the RNA recognition motif of PRC2 complex might help these RNAs bind to the PRC2 complex more easily. The same regulatory pattern was found in mice as well.